Challenges in Treating Mycobacterium chelonae/abscessus Prosthetic Joint Infection. (June 2022) - Singh, Divita; Johnson, Mikayla; Kitchens, Caleah S.; Boone, Andrew
Prosthetic joint infections (PJIs) remain a major complication of arthroplasty, most of which are caused by Staphylococcus aureus and gram-negative bacteria. Unfortunately, cultures are false negative in upward of 7 percent of patients with suspected PJIs, and commonly in infections caused by rare rapidly growing mycobacterium (RGM) species. Guidelines recommend 6 months of antimycobacterial therapy for bone diseases caused by RGM, with empiric therapy consists of an oral macrolide (clarithromycin or azithromycin) plus tobramycin and imipenem-cilastatin. Definitive treatment of PJI due to RGM should be guided by antimicrobial susceptibility, however, most microbiology laboratories are unable to differentiate between M. chelonae and M. abscessus . Furthermore, treatment of M. chelonae PJI is challenging due to multidrug resistance and the dearth of oral antibiotics for therapy. This case report investigates a patient with PJI caused by M. chelonae and M. abscessus . The initial treatment with imipenem-cilastatin was complicated by drug induced seizures, further limiting therapy options.